Analisis Modal Sosial dalam Pengentasan Kemiskinan Melalui Program E-Warung Di Kota Kediri - Taufik Alamin; Ade Abizar Uyun (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2022)
Poverty is one of the main problems in a government, not only developing countries, developed countries also have poverty problems even though the poverty rate is of course very different. Responding to President Joko Widodo's direction, the Ministry of Social Affairs formulated an e-Warung policy as a place for taking non-cash Food Assistance through collaboration with other parties (Bulog and Banks). The purpose of non-cash assistance is indeed directed at efforts to fulfill nutrition. In addition, the purpose of holding an e-Warung is an attempt to facilitate empowerment for beneficiary families (KPM) through joint group efforts (KUBE). Kediri City, which includes three sub-districts (Kota, Islamic Boarding School, Mojoroto) has sixteen e-Warung points. Each e-Warung has a different management system. This research is within the scope of the City of Kediri, is a qualitative research, using a case study approach that uses a conceptual framework to describe and fully understand e-Warung to find problems to produce solutions. The goal to be achieved in this research is the realization of the functions and objectives of the e-Warung as a policy in the form of empowerment.